Academic Instructional Leadership According to the Ten Royal Virtues - Ladawan, Kittayakorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of this article is to study the academic leadership especially according to the ten royal virtues since the leaders should rely on leadership as a driving force for organizational development, meanwhile the leaders should be aware of the Buddha dharma principles for successful administration based on the ten royal virtues which can be used for leadership development.